Alocação de recursos em redes de sensores IoT híbrida ZigBee e LoRa - Santos, Willian Garcia Viega dos (2020)
With the growth in the number of devices connected to IoT networks, the requirements of communication reliability and efficient use of energy have increased. This research proposes a hybrid network topology for IoT sensors by using mesh and star topologies. This hybrid network aims to improve the efficiency of energy consumption and to ensure greater network coverage for sensor allocation. For network planning, defining mesh network clusters and star network points, a fusion of Genetic Algorithms and K-Medoids Algorithms was proposed. For the allocation of resources in the mesh (ZigBee) and star (LoRa) networks, Dijkstra and Genetic Algorithms were proposed, respectively, in order to reduce the energy consumed by the network. Experimental data collected through active intervention in the field were used to plan the proposed network topology. A network consisted of 380 sensors spread throughout Vitória-ES was planned to connect to a gateway in Vila Velha-ES. After executing the planning and resource allocation algorithms, 26 mesh networks were defined and the resources were allocated in each sensor to save energy and ensure communication